Encephalopathy caused by novel mutations in the CMP‐sialic acid transporter, SLC35A1. Issue 11 (29th August 2017) - Ng, Bobby G.; Asteggiano, Carla G.; Kircher, Martin; Buckingham, Kati J.; Raymond, Kimiyo; Nickerson, Deborah A.; Shendure, Jay; Bamshad, Michael J.; ,; Ensslen, Matthias; Freeze, Hudson H.
Abstract : Transport of activated nucleotide‐sugars into the Golgi is critical for proper glycosylation and mutations in these transporters cause a group of rare genetic disorders termed congenital disorders of glycosylation. We performed exome sequencing on an individual with a profound neurological presentation and identified rare compound heterozygous mutations, p.Thr156Arg and p.Glu196Lys, in the CMP‐sialic acid transporter, SLC35A1 . Patient primary fibroblasts and serum showed a considerable decrease in the amount of N‐ and O‐glycans terminating in sialic acid. Direct measurement of CMP‐sialic acid transport into the Golgi showed a substantial decrease in overall rate of transport. Here we report the identification of the third patient with CMP‐sialic acid transporter deficiency, who presented with severe neurological phenotype, but without hematological abnormalities.